The Influence of Office Layout on Employee Performance at the Barombong District Office - Muh. Nasrullah; St. Sriwahyuni Muksin; Jamaluddin Jamaluddin; Muh. Darwis (Jurnal Office, 2022)
Performance is the result of work and work behavior that has been achieved in completing the assigned tasks and responsibilities within a certain period. The purposes of this study are: 1) To find out the description of office layout at the Barombong District Office, 2) To find out how the performance of employees at the Barombong District Office, 3) To find out whether there is an influence of office layout on employee performance at the Barombong District Office. Data collection used primary data obtained from employees of the Barombong sub-district office who were then used as respondents using a saturated sample where all members of the population were used as samples from the results of primary data collected through distributing questionnaires. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis. The results showed that partially good office layout had a positive and significant effect on employee performance so that the proposed hypothesis was accepted. This study has a strong influence between the two variables compared to previous studies which only had a moderate effect.